GROWTH AND PRODUCTION OF TWO VARIETIES OF PULUT CORN (Zea mays ceratina kulesh) AT DIFFERENT DOSAGES OF NPK FERTILIZER - Yustisia, Dian; Alamsyah, Ridha (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Corn is the second important commodity after rice in Indonesia. To obtain good corn production results, appropriate fertilizer application is needed. NPK fertilizer treatment with doses of 0 g (PO), 5 g (P1), 10 g (P2), and 15 g (P3) per planting, given at 10 days after planting and 35 days after planting. The method of fertilization is done by immersing it in an array around the base of the plant roots as deep as 5 to 10 cm. Harvesting is done on local corn varieties when the corn plants enter 60 days after planting. As for the corn pulut variety, it was carried out 75 days after planting. Plant observation include plant height, number of leaves, cob length, cob weight, and weight of 100 seeds for each treatment. The use of NPK fertilizer doses showed the best results in the P2(10gram)/plant treatment. The growth and production of two varieties of pulut corn plants that gave the best results were the purple corn variety (V1). The interaction between the two varieties and the dose of NPK fertilizer was not significant for any of the corn plant parameters observed.